Properties of a novel quaterpolymer P(3HB/4HB/3HV/3HHx). (28th September 2016) - Volova, Tatiana G.; Vinogradova, Olga N.; Zhila, Natalia O.; Peterson, Ivan V.; Kiselev, Evgeniy G.; Vasiliev, Alexander D.; Sukovatiy, Aleksey G.; Shishatskaya, Ekaterina I.
Abstract: Cupriavidus eutrophus В10646 was used to synthesize a series of polyhydroxyalkanoate (PHA) quaterpolymers composed of the short-chain-length 3-hydroxybutyrate (3HB), 4-hydroxybutyrate (4HB), and 3-hydroxyvalerate (3HV) and the medium-chain-length 3-hydroxyhexanoate (3HHx). The molar fraction of 3HB in the quaterpolymers varied between 63.5 and 93.1 mol.%, 3HV – between 1.1 and 24.6 mol.%, 4HB – between 2.4 and 15.6 mol.%, and 3HHx – between 0.4 and 4.8 mol.%. The properties of PHA quaterpolymers were significantly different from those of the P(3HB) homopolymer: they had much lower degrees of crystallinity (up to 30–45%), and lower melting points and thermal decomposition temperatures, with the interval between these temperatures remaining practically unchanged. Films prepared from PHA quaterpolymers were rougher and more porous than P(3HB) films; they showed higher values of elongation at break (up to 6–113%), i.e. were more elastic. Films prepared from PHA quaterpolymers were biocompatible and had no toxic effect on mouse fibroblast NIH 3T3 cells. Graphical abstract: Highlights: P(3HB-co-3HV-4HB-3HHx) quaterpolymers were synthesized using C. eutrophus B10646. Quaterpolymers had much lower degrees of crystallinity than P(3HB). Films prepared from quaterpolymers were more elastic than P(3HB). The biocompatibility of quaterpolymers was proved in the culture of mouse fibroblast.